UPAYA MENCIPTAKAN BAHAN AJAR, LINGKUNGAN BELAJAR DAN SISTEM BELAJAR MENGAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII SEKOLAH SMPN 36 MERANGIN - Nuzli, Muhammad; Agusmanto, Ardinsyah; Laili, Najmi; Lavivi, Siddik; Pranoko, Adi (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
So far, teachers have made many innovations in educational planning to help teachers and students in creating comprehensive and organizing education so that historical education is expected to be carried out optimally. However, how to design educational procedures and models that can generate student motivation itself is still very rarely carried out. In this case, educational practices tend to ignore students' ideas, concepts and thinking skills. The activities of the teacher are more prominent than the students and are limited to mere memorization. This research was attempted to fulfill the task of the learning technology course with the mentor lecturer Muhammad Nuzli's father, Meter. PD. I. This research is qualitative research and uses several methods of collecting information, namely, observation, interviews and documentation. There are also the results of this research that can be known about1) teaching materials for Islamic religious learning for class VII students of SMPN 36 Merangin. 2) the condition of the Islamic religious learning area for seventh grade students of SMPN 36 Merangin. 3). the teaching and learning process of Islamic religious learning for seventh grade students of SMPN 36 MeranginABSTRAKSepanjang ini guru sudah banyak melaksanakan inovasi dalam perencanaan pendidikan buat menolong guru serta siswa dalam mengkreasi menyeluruh serta mengorganisasi pendidikan sehingga diharapkan pendidikan sejarah bisa dilaksanakan secara maksimal. Namun, bagaimana merancang prosedur dan model pendidikan yang dapat membangkitkan motivasi siswa itu sendiri masih sangat jarang dilakukan. Dalam hal ini, praktik pendidikan cenderung mengabaikan ide, konsep, dan keterampilan berpikir siswa. Aktivitas guru lebih menonjol daripada siswa dan terbatas pada hafalan belaka. Riset ini dicoba buat penuhi tugas mata kuliah teknologi pembelajaran dengan dosen pengampu bapak Muhammad Nuzli, M. PD. I. riset ini ialah riset kualitatif serta memakai sebagian metode pengumpulan informasi ialah, observasi, wawancara serta dokumentasi. Ada pula hasil riset ini bisa dikenal tentang 1) bahan ajar pembelajaran agama islam siswa kelas VII SMPN 36 Merangin. 2) keadaan area belajar pembelajaran agama islam siswa kelas VII SMPN 36 Merangin. 3). proses belajar mengajar pembelajaran agama islam siswa kelas VII SMPN 36 Merangin